2017
DOI: 10.1371/journal.pone.0180606
|View full text |Cite
|
Sign up to set email alerts
|

Geographical distribution of Culicoides (DIPTERA: CERATOPOGONIDAE) in mainland Portugal: Presence/absence modelling of vector and potential vector species

Abstract: Vector-borne diseases are not only accounted responsible for their burden on human health-care systems, but also known to cause economic constraints to livestock and animal production. Animals are affected directly by the transmitted pathogens and indirectly when animal movement is restricted. Distribution of such diseases depends on climatic and social factors, namely, environmental changes, globalization, trade and unplanned urbanization. Culicoides biting midges are responsible for the transmission of sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 41 publications
4
7
0
Order By: Relevance
“…In our maps, C. imicola appeared to be present all year round, as it can be found on the southern coast of Spain during January and February. This agrees with previous analyses of the start of the vector season in Europe, where C. imicola was found to be present during the winter months in southern Spain and central and southern Portugal [ 65 ]. The predicted probability of presence shown in our maps are in agreement to the distribution models made for Spain by Ducheyne et al [ 56 ], Calvete et al [ 55 ] and Peters et al [ 70 ], and for France, where the Presence areas for the species are mainly located in the coastal regions of Corsica and VAR department [ 15 ].…”
Section: Discussionsupporting
confidence: 92%
“…In our maps, C. imicola appeared to be present all year round, as it can be found on the southern coast of Spain during January and February. This agrees with previous analyses of the start of the vector season in Europe, where C. imicola was found to be present during the winter months in southern Spain and central and southern Portugal [ 65 ]. The predicted probability of presence shown in our maps are in agreement to the distribution models made for Spain by Ducheyne et al [ 56 ], Calvete et al [ 55 ] and Peters et al [ 70 ], and for France, where the Presence areas for the species are mainly located in the coastal regions of Corsica and VAR department [ 15 ].…”
Section: Discussionsupporting
confidence: 92%
“…In addition, prior studies established a direct relationship between Culicoides abundance measured in traps and the probability of Bluetongue virus occurrences (Calvete et al 2008, Guis et al 2012. In agreement with the literature summarized in Table 1, C. imicola is highly abundant in south-western regions of Spain during summer; has longer adult activity seasons and prefers higher temperatures, probably related with its Afrotropical preferences (Ortega et al 1999;Miranda et al 2004Miranda et al , 2007Talavera et al 2015;Ramilo et al 2017). Its peaks of adult activity occur between 16 and 18°C, and the species is absent in sites with cold winters Mellor 1994, Venter et al 2019).…”
supporting
confidence: 78%
“…Breeding site preferences of Pulicaris complex are ill-defined and likely flexible [81]. Our finding that altitude is quite important for Pulicaris occurrence is consistent with previous work [37,71], although few studies have examined this complex on the Iberian Peninsula [37,74]. Our results suggest that altitude should be taken into account when modeling Pulicaris complex distribution.…”
Section: Culicoides Spp Distribution Modelssupporting
confidence: 89%
“…We did not require an indication of the direction of variables' importance because many studies using parametric techniques have identified factors that drive Culicoides spp. ecology and have described how those factors interact with Culicoides distribution or abundance [22,23,26,[69][70][71][72][73][74]. Although RF tolerates variable collinearity, some studies have shown that correlated variables can be favored in the process of growing trees [75].…”
Section: Culicoides Spp Distribution Modelsmentioning
confidence: 99%